IEEE 802.11 simsiz giriş şəbəkələrinin səmərəliliyinin artırılması üçün yeni metodların tədqiqi - Məmmədli, Məzahir (My University, 2024)
In the dissertation, a channel model for the WLAN cell based on the IEEE 802.11n/ac standard has been developed and investigated, and the following results were obtained: - The main criteria and approaches used in radio planning are reviewed. Key practical issues in the design of WLANs are analyzed. - A model describing the communication channel from the perspective of the transmission duration of the data frame is proposed. The model expresses the dependence of the frame transmission duration on the signal-to-noise ratio. In this case, the function is monotonic, continuous, and smooth.
Investigation of new methods to improve the efficiency of IEEE 802.11 wireless access networks
Keywords: IEEE Network; WLAN